(3GdhQbI GdJLGQjI (B"CPFF" : s (3CHYK LOjO ddChQGb GdJLGQjI aj CYbGH GdCReI GdeGdjI GdYGdejI? (B/ s - (3CHh GdYjfjf, eUWai(B.s ((3OHj (B: s (3eQcR GdHMhK h GdOQGSGJ HCcGOjejI TQWI OHj,s, 2012)
(3dLCJ GdTQcGJ GdJLGQjI hGdUfGYjI Edi GSJNOGe GdhQbI GdJLGQjI, ef CLd GdJSgjd GdJehjdj (BCPFF(3, hPdc dJOHjQ GMJjGLGJgG ef GdSjhdI GdfbOjI aj Xd JQGLY GSJYeGd GdChQGb GdJLGQjI GdJbdjOjI YbH XghQ GdCReI GdeGdjI Ydi GdYGde YGe (B2008. (3Ef GdWHjYI GdbGfhfjI ddhQbI GdJLGQjI ddJSgjd GdJehjdj JLYdgG CbQH eG Jchf dMUGf WQhGOI, GdPj jSeM deUOQgG HONhd YGde GdGSJKeGQ GdeGdj, hGdfbOj, eJNajG aj fehPL bGfhfj jJjM dg GdgQhH ef GdQbGHI, hHGdJGdj Jdbj HJOGYjGJ GbJUGOjI, heGdjI egeI Ydi GdShb GdfbOj ddOhdI(B. (3dgPG, aEf GdWHjYI GdbGfhfjI GdaQjOI ddhQbI GdJLGQjI ddJSgjd GdJehjdj JSJhLH hVY JfXje bGfhfj NGU dEUOGQgG, hGdGSJKeGQ ajgG, Ydi fMh jJfGSH eY NUGFUgG GdeejRI, hJHYGJgG GdGbJUGOjI Ydi Shb GdGSJKeGQ GdfbOj, hGdeGdj aj OhdI GdEeGQGJ GdYQHjI GdeJMOI(B.s
Keywords: (3GdChQGb GdJLGQjIs -- (3bhGfjf h JTQjYGJ(B.s